Variability of contemporary vegetation around Petuniabukta, central Spitsbergen - Prach, K. (Karel); Klimešová, J. (Jitka); Košnar, J.; Redčenko, O.; Hais, M. (Polish Polar Research, 2012)
Vegetation was described in various spatial scales in the area of 37.8 km(2) including distinguishing vegetation units, vegetation mapping, recording phytosociological releves (53), and completing species lists of vascular plants (86), mosses (124) and lichens (40). Phytosociological releves were elaborated using ordination methods DCA and CCA. The releves formed clusters corresponding well to a priori assigned vegetation units. Slope and stoniness significantly influenced the vegetation pattern. Despite the high latitude (nearly 80 N), the vegetation is rather rich in species. Non-native species do not expand. The moss Bryum dichotomum is reported for the first time from Svalbard archipelago.